Earth Observation of Global Change The Role of Satellite Remote Sensing in Monitoring the Global Environment - Chuvieco, Emilio; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Global Change is increasingly considered a critical topic in environmental research. Remote sensing methods provide a relevant tool to monitor global variables, since they offer a systematic coverage of the Earth Surface, at different spatial, spectral and temporal resolutions. The data provided by Earth Observation Satellites are being operationally used for monitoring atmospheric conditions, ice sheets and glaciar movements, crop dynamism and land use changes, deforestation and desertification processes, as well as water conditions. The book includes an analysis of the leading missions in global Earth observation, and then reviews the main fields in which remote sensing methods are providing vital data for global change studies. Audience: Academic libraries, practitioners, professionals, scientists, researchers, lecturers, tutors, graduates, undergraduates
International Efforts on Global Change Research -- NASA Earth Observation Satellite Missions for Global Change Research -- The Role of the European Space Agency in Global Change Observations -- Ozone in the Atmosphere -- Remote Sensing of Land-Cover and Land-Use Dynamics -- Satellite Observation of Biomass Burning -- Satellites Oceans Observation in Relation to Global Change -- Observing Surface Waters for Global Change Applications -- Remote Sensing of Terrestrial Snow and Ice for Global Change Studies.
Keywords: GEOLOGY; METEOROLOGY; REMOTE SENSING; GEOGRAPHICAL INFORMATION SYSTEMS; ENVIRONMENTAL TOXICOLOGY; ENVIRONMENTAL POLLUTION; GEOSCIENCES; REMOTE SENSING/PHOTOGRAMMETRY.; GEOGRAPHICAL INFORMATION SYSTEMS/CARTOGRAPHY.; METEOROLOGY/CLIMATOLOGY.; GEOLOGY; ECOTOXICOLOGY; WASTE WATER TECHNOLOGY / WATER POLLUTION CONTROL / WATER MANAGEMENT / AQUATIC POLLUTION